PELATIHAN SPSS UNTUK ANALISIS DATA PENELITIAN TINDAKAN KELAS - Nur Afandi; Herlin Fransiska; Siska Yosmar; Dyah Setyo Rini; Winalia Agwil; Baki Swita (Jurnal Berdaya Mandiri, 2022)
The implementation of Classroom Action Research (CAR) in SMA 8 Bengkulu City is not optimal. The problem is the teacher's skills in data analysis, such as: methodology, depth of analysis, and statistical analysis tools is low. Statistical analysis commonly used is descriptive statistics rather than inferential statistics. The solution is to carry out data analysis training for classroom action research using SPSS software. The activity has 3 (three) stages: 1. Preparation stage: collect the information, tracking, and survey of teacher needs, which includes problems faced by teachers in analyzing classroom action research data. 2. Implementation stage: training on SPSS software for data analysis. 3. Evaluation stage: practical tests for training participants. Based on evaluation, it concluded that the teacher's skill in data analysis had increased. keyword: Training, CAR, SPSS